2002
DOI: 10.1046/j.1365-201x.2002.00955.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory mechanics in mice: strain and sex specific differences

Abstract: To assess the contribution of genetic background to respiratory mechanics, we developed a ventilator unit to measure lung function parameters in the mouse. We studied two commonly used inbred mice strains originating from Mus musculus domesticus (C57BL/6 and C3HeB/FeJ) and a third strain derived from Mus musculus molossinus [Japanese fancy mouse 1 (JF1)]. The ventilator allows for accurate performance of the different breathing manoeuvres required for measuring in- and expiratory reserve capacity, quasi-static… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 20 publications
1
50
0
Order By: Relevance
“…Furthermore, as several acute and chronic inflammatory pulmonary disorders, which include ALI and acute respiratory distress syndrome (ARDS), are influenced by gender, [ 13 ], [ 14 ], [ 15 ], [ 16 ], [ 17 ], [ 18 ], [ 19 ], [ 20 ], [ 21 ] and [ 22 ] age, [ 23 ], [ 24 ], [ 25 ], [ 26 ] and [ 27 ] or gender-age interactions, [ 28 ], [ 29 ] and [ 30 ] we designed our study to evaluate the influence of these comodifiers on postulated nmMLCK2-mediated increases in vascular paracellular transport. This is supported by findings in mice, which like humans, have varying respiratory properties that differ between sexes [ 31 ], [ 32 ] and [ 33 ] and with age, [ 34 ] and [ 35 ] information often neglected when describing a pulmonary phenotype.…”
Section: Translational Significancesupporting
confidence: 49%
See 1 more Smart Citation
“…Furthermore, as several acute and chronic inflammatory pulmonary disorders, which include ALI and acute respiratory distress syndrome (ARDS), are influenced by gender, [ 13 ], [ 14 ], [ 15 ], [ 16 ], [ 17 ], [ 18 ], [ 19 ], [ 20 ], [ 21 ] and [ 22 ] age, [ 23 ], [ 24 ], [ 25 ], [ 26 ] and [ 27 ] or gender-age interactions, [ 28 ], [ 29 ] and [ 30 ] we designed our study to evaluate the influence of these comodifiers on postulated nmMLCK2-mediated increases in vascular paracellular transport. This is supported by findings in mice, which like humans, have varying respiratory properties that differ between sexes [ 31 ], [ 32 ] and [ 33 ] and with age, [ 34 ] and [ 35 ] information often neglected when describing a pulmonary phenotype.…”
Section: Translational Significancesupporting
confidence: 49%
“…6 The gene also encodes a ~19-kDa protein known as kinase-related protein (KRP) or telokin that is transcribed from the C-terminal exons [30][31][32][33], and it serves to stabilize actin filaments. 7 In addition to smooth muscle myosin light chain kinase (smMLCK) and KRP, 5 splice variants were identified that use the start codon of the 210-kDa isoform, but they have internal exon deletions compared with the longest variant (nmMLCK1).…”
Section: Translational Significancementioning
confidence: 99%
“…Phenotyping the lung function in the mouse has revealed strain specific differences between parameters such as lung volumes, compliance of the lung, respiratory system resistance, and ventilatory responses (10,15,19,21,(25)(26)(27), to name a few. However, as reported by Reinhard et al (19), there is no direct evidence that any one strain exhibits directly correlated relationships between lung function parameters, which suggests that they are not necessarily coinherited.…”
Section: Discussionmentioning
confidence: 99%
“…5) (Schulz et al, 2002). Figure 6 shows the airway deformations of control and asthma model mouse at FRC and VT. At FRC, the diameter was larger in asthma group than in control group.…”
Section: Localized Morphometric Deformation Of Healthy Micementioning
confidence: 99%
“…FRC (functional residual capacity) was defined as the lung volume at euthanasia, and the lung volume could be externally regulated using a syringe connected to the trachea. The volume of TV (at end of tidal inspiration) and TLC (total lung capacity) was defined as the sum of FRCϩ250 and 800 mL, respectively (Schulz et al, 2002).…”
Section: Quasi-static Inflation Processmentioning
confidence: 99%